2020
DOI: 10.1186/s12931-020-01362-8
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 regulates a prolonged adaptation response to environmental dust exposure-induced lung disease

Abstract: Background: Environmental organic dust exposures enriched in Toll-like receptor (TLR) agonists can reduce allergic asthma development but are associated with occupational asthma and chronic bronchitis. The TLR adaptor protein myeloid differentiation factor88 (MyD88) is fundamental in regulating acute inflammatory responses to organic dust extract (ODE), yet its role in repetitive exposures is unknown and could inform future strategies. Methods: Wild-type (WT) and MyD88 knockout (KO) mice were exposed intranasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Surprisingly, FFAR4 had a significant and independent effect on cell influx ( Figure 1 d) [ 1 , 2 ]. Entrapment of immune cells in the mesenchyme has been demonstrated in Myd88 -null mice repetitively exposed to DE [ 33 , 43 ]. These published studies revealed no significant changes to cells in the BAL but with significant histopathologic changes in the Myd88 -deficient mice, including immune cell entrapment and epithelial dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, FFAR4 had a significant and independent effect on cell influx ( Figure 1 d) [ 1 , 2 ]. Entrapment of immune cells in the mesenchyme has been demonstrated in Myd88 -null mice repetitively exposed to DE [ 33 , 43 ]. These published studies revealed no significant changes to cells in the BAL but with significant histopathologic changes in the Myd88 -deficient mice, including immune cell entrapment and epithelial dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, epithelial progenitor populations in the lung also express H2k1 and drive barrier restoration [ 81 ]. Lymphocyte antigen 96 ( Ly96 ), also called myeloid differentiation factor 2 (Md2), dimerizes with TLR4 to recognize LPS and initiate MyD88 signaling cascades driving pro-inflammatory gene expression in response to swine dust exposure [ 33 , 82 , 83 ]. MyD88 KO mice repetitively exposed to DE exhibited significantly reduced chemokine and cytokine release, dampened BAL cell influx, and epithelial dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic dust extracts (ODE) from animal feeding operations induce a profound inflammatory response both in vitro and in vivo with several prior studies demonstrating strong roles for Toll-like receptor (TLR) and MyD88 signaling pathways ( Charavaryamath et al., 2005 ; Charavaryamath et al., 2008 ; Charavaryamath et al., 2008 ; Poole et al., 2015 ). In airway epithelial cells, these exposures induce pro-inflammatory cytokine release, neutrophil influx, mucus metaplasia, alter tight junction expressions, disrupt cellular migration, and slow ciliary beat frequency ( Wyatt et al., 2008 ; Bhat et al., 2019 ; Johnson et al., 2020 ; Shrestha et al., 2021 ). It has also been demonstrated that CO 2 concentrations differentially effect the magnitude of inflammatory responses to ODE and various TLR ligands ( Schneberger et al., 2015 ; Schneberger et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that exposure to swine production units containing organic dust and H 2 S induces airway epithelial damage ( Charavaryamath et al., 2008 ). ODE is known to induce alterations in several tight junction components including occludin protein ( Johnson et al., 2020 ). However, the effect of simultaneous exposure to organic dust and H 2 S on the airway epithelial tight junction proteins is unknown.…”
Section: Introductionmentioning
confidence: 99%